1997
DOI: 10.1055/s-0038-1657688
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Reversibly Disaggregates Fibrin Fibers

Abstract: SummaryUltrasound accelerates fibrinolysis in vitro and in vivo, primarily through non-thermal mechanisms including cavitation. We have previously observed that ultrasound reversibly increases flow through fibrin gels, a property primarily determined by the structure of the fibrin matrix. Therefore, the effect of ultrasound on the ultrastructure of fibrin gels was examined using scanning electron microscopy. Non-cross- linked fibrin gels were fixed and prepared for microscopy before, during and after exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
152
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(157 citation statements)
references
References 42 publications
4
152
1
Order By: Relevance
“…Several in vitro studies suggest that US directly changes the fibrin structure, inducing the better penetration of tPA into the thrombus. 30,31 In the present study, we demonstrated that US enhanced the pharmacological lysis of platelet-rich thrombus, probably without direct influence on the structure of thrombus, indicated by the angiographic and histological data for the US alone group. Therefore, we consider that US accelerates the mixing of tPA into the thrombus in vivo by microstreaming.…”
Section: Discussionsupporting
confidence: 48%
“…Several in vitro studies suggest that US directly changes the fibrin structure, inducing the better penetration of tPA into the thrombus. 30,31 In the present study, we demonstrated that US enhanced the pharmacological lysis of platelet-rich thrombus, probably without direct influence on the structure of thrombus, indicated by the angiographic and histological data for the US alone group. Therefore, we consider that US accelerates the mixing of tPA into the thrombus in vivo by microstreaming.…”
Section: Discussionsupporting
confidence: 48%
“…This mechanism would seem to explain the enhancing effect of pulsed-HIFU on tPA-mediated thrombolysis observed in our in vitro [17] study, and similarly could explain the results in the present study. These results are supported by additional studies in purified fibrin gels, where ultrasound exposures caused reversible fiber disaggregation [23], and consequently improved fluid flow through the gels [24]. When the same exposures were carried out in blood clots, improved penetration of tPA was observed, in comparison to untreated clots [25].…”
Section: Discussionmentioning
confidence: 59%
“…High-frequency, low-intensity US can be used safely in many medical applications but has no lytic effect. However, the combination of directed US with the local administration of thrombolytic agents accelerates the thrombolytic process (24).…”
Section: Discussionmentioning
confidence: 99%